PTU-122 A Gmp Treg Expansion Protocol Restores Treg Suppressor Function In End-stage Liver Disease; Implications For Adoptive Transfer Therapy. (9th June 2014) - Safinia, N; Vaikunthanathan, T; Fraser, H; Scotta, C; Lechler, R; Lombardi, G
Abstract : Introduction: Long-term survival in liver transplant recipients remains suboptimal because of the morbidity and mortality associated with the long-term use of immunosuppression (IS). However, IS weaning early post liver transplantation (LT) has largely been unsuccessful, supporting the need for active tolerance induction strategies. CD4 + CD25 + FOXP3+ (Tregs) play an important role in immunoregulation and have been shown in animal models to promote transplantation tolerance. Phase I trials in bone marrow transplantation have shown that ex vivo expanded Tregs have an excellent safety profile, which is encouraging for the broader application of these cells. The clinical trial, ThRIL, soon to be initiated at King's College London, aims to investigate the therapeutic potential of Tregs in the setting of LT. We have devised a GMP compatible protocol that ensures the successful isolation and expansion of a functional and stable human Treg population in preparation for this trial. Methods: Tregs were isolated from 150ml of blood from patients with end-stage liver disease by a CliniMACS-based GMP isolation technique and expanded using anti-CD3/CD28 beads, IL-2 and rapamycin. Results: A 580-fold expansion of pure Tregs was achieved (97.4% CD4 + CD25 + and 0.008% CD8 + cells) and the cells maintained FoxP3 expression (99.6% of the CD4 + CD25 + cells express FoxP3). The populations of Tregs obtained were also stable and did not convert to Th17 cells when cultured in the presence of pro-inflammatory stimuli. This protocol further proved to be ideal for the expansion of Tregs from patients with liver disease in view of restoring the Tregs' suppressive function (1:1 ratio – expanded Tregs 91.1% vs. freshly isolated Tregs 28.6% suppression, 1:10 ratio – 80.7% vs. 20.8% respectively). Based on these findings, we subsequently conducted an in-depth phenotypic characterisation of freshly isolated Tregs in order to delineate a population responsible for the apparent lack of suppressive function. An investigation into the possible mechanisms is currently ongoing. Conclusion: The feasibility of Treg based therapy is now widely accepted, provided that tailor-made clinical grade procedures for isolation and ex-vivo cell handling are available. Our rapamycin-based protocol is ideal in this setting as it not only satisfies the rigours of GMP manufacturing standards, but also derives a population of Tregs that is stable and functionally superior compared to freshly isolated Tregs. Disclosure of Interest: None Declared.